DIGITALIZATION OF COFFEE SME IN LAKE TOBA AREA - Hendra Hendra; Vinsensius Matondang; Bilson Pandiangan; Binsar Sihombing (LPSDI Bina Patria, 2022)
The research studies Coffee SME Strategy’s Implementation in Lake Toba Area in facing challenges posed by Covid-19 pandemic. The Data is collected using google form and focus group discussion, originates from 6 districts of Lake Toba Area, namely Toba, Humbang Hasundutan, Samosir, Taput, Karo and Simalungun districts, would be compared to SME data nationally during the pandemic period. It is found that Coffee SME is able to survive and develop in the midst of pandemic, by applying strategy shift in their enterprise, especially in digitalization, utilizing integrated digital marketing, building marketplace existence, and carrying out continuous innovation.